Imaging Torfajökull's Magmatic Plumbing System With Seismic Interferometry and Phase Velocity Surface Wave Tomography. Issue 3 (25th March 2019) - Martins, J. E.; Ruigrok, E.; Draganov, D.; Hooper, A.; Hanssen, R. F.; White, R. S.; Soosalu, H.
Abstract: Torfajökull volcano, Iceland, has not erupted since 1477. However, intense geothermal activity, deformation, and seismicity suggest a long‐lasting magmatic system. In this paper, we use ambient noise tomography to image the magmatic system beneath Torfajökull volcano. One hundred days of ambient noise data from 23 broadband seismometers show the consistent presence of double‐frequency microseism noise with significant power between ∼0.1 and 0.5 Hz. Beamforming results indicate microseism noise with persistent higher energy propagating from west and SE directions and apparent velocities below 3 km/s. We use ambient noise seismic interferometry to retrieve Rayleigh waves, and we introduce a method to estimate the reliability of the retrieved surface waves. We find stable estimation of surface wave phase velocities between 0.16 and 0.38 Hz. Azimuthal velocity variations show a trend of higher velocities in the NE/SW direction, the strike of the rift zone intersecting Torfajökull, and orientation of erupted lavas on a NE‐SW fissure swarm. Tomographic results indicate low‐velocity anomalies beneath the volcano caldera (between −5% and −10%) and even lower velocity variations in the southeast and southwest study area (below −10%), outside the volcano caldera. Low anomalies may indicate the existence of hot material, more prominent outside the caldera outskirts. High‐velocity variations (between 5% and 10%) outline the volcano caldera between 4‐ and 5‐km depth and more pronounced velocities (between 10% and 15%) up to 5‐km depth in the north of the volcano caldera. We interpret the former as possible caldera collapse structure and the latest as solidified intrusive magma from the old preferred magma paths. Plain Language Summary: Magmatic plumbing systems' characterization is one of the pillars for predicting volcanic eruptions. While most of the active volcanoes are being currently monitored, less is known about volcanoes that had not erupted recently. Torfajökull volcano, Iceland, has not erupted since 1477. However, intense geothermal activity, deformation, and seismicity suggest a long‐lasting magmatic system. We use ambient noise to produce a tomographic image of the magmatic system beneath Torfajökull volcano. This technique allows us to detect velocity variations/contrasts due to changes in composition, density, temperature, or pressure in the subsurface.We identify high‐velocity variations outlining the volcano caldera between 4‐ and 5‐km depth and more pronounced high‐velocities at shallower depths in the north of the volcano caldera. We interpret the former as possible caldera collapse structure and the latest as solidified (and dense) intrusive magma from the old preferred magma paths. The tomographic results also indicate low‐velocity anomalies beneath the volcano caldera and even lower‐velocity variations in the southeast and southwest study area, outside the volcano caldera. The most prominent low‐velocity features are located outside the volcano caldera outskirts. These low anomalies, or deceleration areas of wave velocity, may indicate the existence of hot material (molten or partially molten rock). Key Points: This article presents the first tomographic image (3‐D S  wave velocities) of Torfajökull's magmatic system; we have derived a 3‐D S  wave velocity field from ambient noise tomography We developed a new methodology for phase velocity estimation from retrieved surface waves applied to 100 days of recorded ambient noise We interpret the low‐/high‐velocity anomalies interpreted as molten or partial molten cavities/channels (low) and old dike intrusions/caldera forming (high)